PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2020-2023 - -, Sarina; -, Busra (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2024)
Companies that are looking for investors aim to add capital, so the more capital the company has, the more the company will produce food and drinks so that it can increase the company's profitability. If profitability increases, the value of the company will also increase, as will investment decisions. If you invest more, then company value is getting higher. The aim of this research is to analyze the influence of financial ratios on company value in food and beverage companies registered on BEI in 2020-2023. The method used is a quantitative research method. The conclusion of this research is that there is a partial influence of the DER, TAG and ROE variables on EPS in food and beverage sector companies on the Indonesian Stock Exchange in 2020-2023 and there is an influence of the DER, TAG and ROE variables together or simultaneously on EPS in Food and Beverage Sector Companies on the Indonesian Stock Exchange 2020-2023